2017
DOI: 10.1155/2017/9352015
|View full text |Cite
|
Sign up to set email alerts
|

MMP-2, MMP-9, and TIMP-4 and Response to Aspirin in Diabetic and Nondiabetic Patients with Stable Coronary Artery Disease: A Pilot Study

Abstract: Background High on-aspirin treatment platelets reactivity (HPR) is a significant problem in long-term secondary prevention of cardiovascular events. We hypothesize that imbalance between platelets MMPs/TIMPs results in cardiovascular disorders. We also explored whether chronically elevated blood glucose affects MMP-2/TIMP-4 release from platelets. Materials and Methods Seventy patients with stable coronary artery disease, supplemented with aspirin, participated in this pilot study. The presence of HPR and/or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 57 publications
2
14
1
Order By: Relevance
“…A previous study showed that chronically elevated plasma glucose increases plasma MMP-2 [31]. We were unable to demonstrate any association between MMP levels and the presence of diabetes mellitus in aortic tissue.…”
Section: Discussioncontrasting
confidence: 76%
“…A previous study showed that chronically elevated plasma glucose increases plasma MMP-2 [31]. We were unable to demonstrate any association between MMP levels and the presence of diabetes mellitus in aortic tissue.…”
Section: Discussioncontrasting
confidence: 76%
“…Moreover, MMP-2 is involved in the modification of platelet glycoprotein α IIb β 3 resulting in enhanced platelet adhesion and aggregation 48,49,52. MMP-1 was also indicated to associate with the α IIb β 3 integrin, as suggested by Galt et al, 2002 52. It has been shown that MMP-2 contributed to platelets stimulation and aggregation by non-ADP and non-TXA 2 pathway 51,53…”
Section: Discussionmentioning
confidence: 93%
“…These MMPs rapidly relocate from granule structures inside the platelet to the plasma membrane of activated platelets and enhance P-selectin expression, platelet procoagulant activity, and thrombus formation 4851. Moreover, MMP-2 is involved in the modification of platelet glycoprotein α IIb β 3 resulting in enhanced platelet adhesion and aggregation 48,49,52. MMP-1 was also indicated to associate with the α IIb β 3 integrin, as suggested by Galt et al, 2002 52.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hypoxia (CH) is a condition where the partial pressure of oxygen in the blood is too low to saturate hemoglobin, which may be due to various reasons, including the decrease in the amount of breathable oxygen owing to a reduced barometric pressure [1], often encountered in pilots, mountain climbers, and people living at high altitudes. People inhabiting high altitudes are considered to be exposed to CH and show excessive erythrocytosis and hypoxemia [2,3].…”
Section: Introductionmentioning
confidence: 99%